Regime building in the Levant:The feasibility of cooperation in the Levant Basin - Rishmawi, Johnny (AUC Knowledge Fountain, 2014)
The Levant Basin has become an increasingly hot political issue in the Middle East and Southern Europe. Many countries like Greece, Lebanon, and Cyprus see the basin’s new energy possibilities as an important economic tool to guide their struggling economies. Others like Turkey, Syria and Egypt see it as a threat. Israel, the most advanced country in exploration, has begun the search for the best political and economic partners to develop the country’s energy sector. Due to the geopolitical implications of natural resources, the possible changes in the balance of power that may arise, or the increased potential importance of the region to great powers, this thesis attempts to cover the likely political outcomes of the energy resources by exploring the different possible cooperation schemes among regional powers. This thesis explores cooperation scenarios between Israel and the other regional powers in the Eastern Mediterranean, Egypt, Greece, and Turkey. Using the liberal theories of international regimes and cooperation, this thesis investigates the possibilities of partnerships between the Levant powers and the feasibility of regime formation. We find that the most prominent candidates for fostering natural gas regimes are Israeli-Egyptian and Israeli-Turkish partnerships. To explore their potential, I model regime building, as expressed in Robert Keohane’s theory of international regimes, by applying David Axelrod’s iterated prisoner’s dilemma (IPD) to envision the conditions of cooperation or defection from the proposed partnerships